ABORDAGEM PARA DISTINGUIR OS EFEITOS DO USO E OCUPAÇÃO DO SOLO NAS CARACTERISTICAS DE BACIAS HIDROGRÁFICAS - UM ESTUDO DE CASO - Roselene Maria Schneider; Rosane Freire; Welliton Leandro de Oliveira Boina; Adriana Garcia do Amaral; Célia Regina Granhen Tavares; Paulo Fernando Soares; Bruno Tiago Contessoto Rigo (Colloquium Exactarum, 2014)
Two heterogeneous hidrological basin, located in Maringá-PR, were evaluated in relation to the use and occupation of its land. The basin of Mandacaru creek owns area with high degree of urbanization (85%); the basin of Romeira creek owns agricultural use and occupation. For evaluation, were used the method pins and performed the measure of flow channels under study. As result, it has been found that the presence of urbanization interfers significantly on the structure of the channel, given by the erosion of its margins. During the monitoring period (21 months), erosion of the urban channel presented in the order of centimeters, while the rural channel, 50 Colloquium Exactarum, v. 6, n.4, Nov-Dez. 2014, p.49 –58. DOI: 10.5747/ce.2014.v06.n4.e099 the erosion was in the order of millimeters. Erosive processes presented by the channel were related to high flows that occurred during precipitation. The waterproofing area was responsible for the concentration of rainwater and thus by the energy that promoted the measure erosion.